1979
DOI: 10.1017/s0022172400026346
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an intramammary infusion of endotoxin on experimentally induced mycoplasmal mastitis

Abstract: The infusion of 10 microgram of endotoxin lipopolysaccharide from Escherichia coli into the mammary gland of four cows 16 h before inoculation with ureaplasmas did not prevent, or even diminish, the subsequent ureaplasmal mastitis. There was no reduction in the severity or duration of the inflammatory cell response in milk or in the clinical appearance of the resulting mastitis. Also, the excretion of ureaplasmas was not reduced. A similar experiment with Mycoplasma dispar in two cows demonstrated that endotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Apart from antiphagocytic surface material, bacteria may target PMN with toxins which interfere with the phagocytic process. A special virulence factor may explain why the PMN barrier evoked by intramammary infusion of endotoxin is ineffective in preventing infection of the udder by mycoplasma [73]. Leukotoxins, which are exotoxins produced by many S. aureus strains isolated from mastitis, are able to kill bovine PMN, and consequently are likely to reduce the efficiency of the phagocytic defense during mastitis [74,75].…”
Section: Neutrophils As Inefficient Phagocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from antiphagocytic surface material, bacteria may target PMN with toxins which interfere with the phagocytic process. A special virulence factor may explain why the PMN barrier evoked by intramammary infusion of endotoxin is ineffective in preventing infection of the udder by mycoplasma [73]. Leukotoxins, which are exotoxins produced by many S. aureus strains isolated from mastitis, are able to kill bovine PMN, and consequently are likely to reduce the efficiency of the phagocytic defense during mastitis [74,75].…”
Section: Neutrophils As Inefficient Phagocytesmentioning
confidence: 99%
“…To overcome the phagocytic defense mobilized by the inflammatory response, bacteria which are successful parasites of the mammary gland must have evolved special adaptive mechanisms to cope with the bactericidal efficiency of these leucocytes. The PMN mobilized by the mammary gland are rather efficient against E. coli mastitis, fairly efficient against S. agalactiae and S. aureus mastitis, but much less efficient against S. uberis and Mycoplasma mastitis [73,88]. Even in E. coli, S. agalactiae and S. aureus mastitis, PMN efficiency also seems to depend on the stage of infection.…”
Section: Important Determinants Of the Efficiency Of Neutrophils In Milkmentioning
confidence: 99%
“…These workers have reported that the intramammary infusion of neither E . coli (3,4,24,25) nor A. aerogenes (12) endotoxin resulted in the elevation of the MSCC in contralateral quarters, whereas the MSCC of the infused quarters was markedly elevated.…”
Section: Comparison Of the Responses Of Infused And Non-infused Glandsmentioning
confidence: 96%
“…The clearance of M. pulmonis from the peritoneal cavity of CBA mice was enhanced by increased macrophage numbers but not by increased PMNs (18), and the ability of different strains of M. pulmonis to survive and produce disease within the respiratory tract of CBA mice was correlated to the ability of these mycoplasmas to avoid phagocytosis by AMs (19). Likewise, in a bovine mastitis model, induction of a neutrophilia in response to endotoxin failed to control a secondary challenge with M. dispar or ureaplasmas (20). C57BL/6 mice exposed to nitrogen dioxide and infected with M. pulmonis demonstrated a decreased clearance of respiratory mycoplasmas that could not be correlated with damage to the respiratory epithelium, to mechanical clearance, or to the induction of an acute inflammatory response (21).…”
Section: Cellular Responsesmentioning
confidence: 99%